2017
DOI: 10.1177/0038038517737476
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect Perfection and Wheelchair Bodybuilding: Challenging Ableism or Reproducing Normalcy?

Abstract: This article explores the impact of the binary configuration of disabled bodies as opposite and unequal to able bodies, and whether or not contemporary bodybuilding provides a space where this dualism can be overcome. Drawing on life history interviews with Dan, a professional wheelchair bodybuilder, we consider how his hyper-muscular upper body may position him as a supercrip and thereby reinforce bodily and gender norms. Simultaneously, Dan's powerful, disabled body and a competitive context that applies sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(30 reference statements)
1
5
0
1
Order By: Relevance
“…Thus, these narratives can be overcome through fat activism that showcases fat bodies as acceptable as they are (Bacon and Aphramor 2014;Czerniawski 2015), though overcoming constructions seeing fat as weakness/incompetence has gained less ground (cf. Sparkes, Brighton, and Inckle 2017).…”
Section: Anthropometry and Fatphobiamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these narratives can be overcome through fat activism that showcases fat bodies as acceptable as they are (Bacon and Aphramor 2014;Czerniawski 2015), though overcoming constructions seeing fat as weakness/incompetence has gained less ground (cf. Sparkes, Brighton, and Inckle 2017).…”
Section: Anthropometry and Fatphobiamentioning
confidence: 99%
“…Greenhalgh 2015; Herndon 2014; Saguy and Almeling 2005; Ward, Beausoleil, and Heath 2017; inter alia). This situates fat bodybuilding in parallel to a vein of disruptive scholarship exploring wheelchair bodybuilding as challenging ableism (Sparkes, Brighton, and Inckle 2017). Indeed, fat bodybuilding seeks to address a persistent problem articulated by Levan (2014), who explained that anthropometric prejudice forces bodies to conform to dominant concepts of "ideal proportion as it persists in the representation of the human body through visual means" (119).…”
Section: Why Fat Bodybuilding?mentioning
confidence: 99%
“…e o aparecimento de novos dilemas éticos sobre as possibilidades de vida e morte das pessoas com deficiência (Carneiro;Fleischer, 2018;Diniz, 2003aDiniz, , 2016Fleischer, 2017;Ginsburg, 2001;Simões, 2019). Em outra direção, há os estudos dirigidos aos avanços das tecnologias protéticas e de aparatos técnicos que permitem novas performances esportivas e sua relação com formas de inclusão das pessoas com deficiência (Howe, 2011;Kiuppis, 2018;Pullen et al, 2019;Sparkes;Brighton;Inckle, 2018). Nesse âmbito, é possível verificar o quanto as definições sobre deficiência estão sendo negociadas, contestadas e reproduzidas e como o desenvolvimento de tecnologias -próteses, cadeiras de rodas, etc.…”
Section: Para a Surdezunclassified
“…In research carried out by the author (9,63) it was demonstrated that athletes with newly acquired SCI attempt to adapt to mainstream training environments by learning from experienced athletes with SCI and working with progressive and innovative SCC's. With appropriate guidance, newly impaired athletes were able to learn practical techniques such as i) attaching a golf ball to the end of a rope to throw over the fixed lateral pull down bar to use while in a wheelchair, ii) teaching strapping techniques and the use of Velcro © and adhesives to assist impaired grip in hands, iii) providing alternative ways of transitioning in and out of chairs to use equipment, iv) making use of a partner to assist these transitions.…”
Section: Adapting To Able-bodied Environmentsmentioning
confidence: 99%
“…Research undertaken by the author has revealed that if exclusively constructed through bioscientific and functionalist knowledge, S&C programs risk perpetuating dominant medical understandings of disability (9,63). This is evident in i) an overemphasis on addressing muscular imbalances and maintaining focus on a return to a 'normal' looking and functioning body as opposed to developing muscular functioning bespoke for sports performance, ii) programming assuming a state of linear improvement to a fixed end goal without accounting for individual and/or degenerative impairments, iii) little consideration of the embodied (e.g.…”
Section: Sandc and Reproduction Of The Medical Modelmentioning
confidence: 99%